Complexation studies of 2-hydroxy naphthlidene-3-amino-1.2,4-triazole (HNAT) with some transition metals in aqueous solution - Ercag, Ayse; Ozgur, Mahmure; Canlica, Mevluede; Bozdogan, Abduerrezzak; Tamimy, Vabide (WALTER DE GRUYTER GMBH, 2007)
In this study, the Schiff base 2-Hydroxy Naphthlidene-3-Amino-1,2,4-Triazole (HNAT), derived from 3-Amino-1,2,4-TriAzol (Amitrol) and 2-hydroxynaphthaldehyde, was used. The protonation constants of HNAT in water-ethanol 50%-50% (vol) solution were determined by potentiometric titration at constant temperature, (t=25 +/- 0.1 degrees C) and ionic strength of I=0.1M (NaClO4). The formation constants of HNAT with Cu2+, Ni2+, Mn2+, Fe3+, Cd2+, Cr3+, Ag+, Zn2+ were determined at the same conditions. Purified nitrogen gas was bubbled through the titrated solution to ensure stirring and neutral inert atmosphere. In addition, the solution was stirred magnetically. The solutions were titrated with 0.1 M NaOH in increments of 0.1 mL. The corresponding change in the pH value of the solution was measured. The stoichiometric protonation constants of the ligand were calculated using software called TITFIT developed by Zuberbuhler and Kaden. The values of the protonation constants for the ligand are logK(1)=9.48 (Delta=0.03i3) and logK(2)=7.49 (Delta=0.013). The formation constants of HNAT complexes with Cu2+, Ni2+, Mn2+, Fe3+, Cd2+, Cr3+, Ag+, Zn2+ and species-distribution curves were calculated and plotted using the TITFIT computer program. The order of the stability constants of mononuclear complexes with H2L is Ni2+ > Zn2+ > Fe3+ > Cr3+ > Mn2+ = Co2+ > Cu2+ > Ag.
Keywords: Schiff base; potentiometric titration; TITFIT; Chemistry